Identifying opportunities and gaps in current evaluation frameworks – the knowns and unknowns in determining effective student engagement activity. Issue 6 (18th August 2022) - Wilson, Caroline; Sims, Stuart; Dyer, Jen; Handley, Fiona
Abstract: The higher education sector is under increasing pressure to deliver more and to evidence the fruits of its contribution to society. There is a particular focus on the enhanced engagement of students in order to maximise success, and for this engagement to be achieved equitably across the student body, regardless of demographic backgrounds. This calls for the sector to increase its capability to enhance student engagement in a targeted manner, and to be able to evidence success. The purpose of this article is to critically review, as a result of trialling, frameworks which offer guidance on the structuring of student engagement activity and/or encouraging behaviours associated with student engagement whether at student, teacher or institutional level. We assess the value of these frameworks in practice by identifying opportunities provided by them, reveal gaps in how they support effective student engagement activity, and identify further work for the sector in plugging the guidance gaps that lead to sub-optimal evaluation.